Bahasa Inggris Bahasa Inggris: Bahasa Inggris - Dewa Ayu Anggan Desy Pramitha; Gede Irwandika (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This research analyzes the Yamaha Fazzio advertisement using Roland Barthes’ semiotic approach, emphasizing the interplay between verbal and visual sign in constructing a compelling brand narrative. The Yamaha Fazzio advertisement was chosen as the object of study because of its high popularity in the Indonesian market, as well as its unique branding strategy by targeting young, tech-savvy consumers, making it relevant to current market trends. The analysis examines various scenes from the advertisement, showcasing how components such as color, imagery, and textual cues contribute to the portrayal of the Yamaha Fazzio as a symbol of modernity, innovation, and a dynamic lifestyle. Specifically, this research aims to analyze how the verbal and visual signs in Yamaha Fazzio advertisements convey messages regarding product identity and branding. Additionally, this study applies Wierzbicka's color theory to explore the psychological and cultural associations of color in advertisements, offering deeper insights into how semiotics can shape consumer perception and behavior in digital marketing. By integrating these theoretical frameworks, the research underscores the significance of effective communication in advertising and its impact on engaging a tech-savvy audience.